Personalized surgical therapy - Tonn, J. C.; Thon, N.; Schnell, Oliver; Kreth, F. W. (Annals of Oncology, 2012)
Gliomas are more or less diffuse tumours with the ability to infiltrate surrounding functional brain tissue. Thus, curative surgical treatment generally cannot be achieved. Despite these limitations, open tumour resection represents one of the mainstays in glioma treatment settings. Beyond tissue sampling for accurate histological and molecular genetic evaluation, decompressive effects in the case of space occupying tumours and oncologically relevant cytoreductive effects of microsurgery have been reported in selected patients with glioma of different grades. This paper provides practical considerations in order to integrate the concept of a personalized surgical therapy into the prognostic network of low- and high-grade gliomas, covering both microsurgery and stereotactic biopsy techniques. © The author 2012. Published by Oxford University Press on behalf of the European Society for Medical Oncology. all rights reserved.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Brachytherapy; Glioma therapy; Microsurgery; Molecular neurooncology; Stereotactic biopsy